Ethical questions identified in a study of local and expatriate responders' perspectives of vulnerability in the 2010 Haiti earthquake. Issue 9 (24th February 2017) - Durocher, Evelyne; Chung, Ryoa; Rochon, Christiane; Henrys, Jean-Hugues; Olivier, Catherine; Hunt, Matthew
Abstract : Background: Situations of disaster that prompt international humanitarian responses are rife with ethical tensions. The 2010 Haiti earthquake caused great destruction and prompted a massive humanitarian response. The widespread needs experienced by the population and the scale of the response inevitably rendered priority-setting difficult, and gave rise to ethical challenges. Purpose: This paper presents four ethical questions identified in the analysis of a study on vulnerability and equity in the humanitarian response to the 2010 Haiti earthquake. Methods: Using interpretive description methodology, the interdisciplinary research team analysed 24 semi-structured in-depth interviews conducted with expatriate and Haitian health workers and decision-makers involved in the response. Results: Ethical questions identified through the analysis were: (1) How should limited resources be allocated in situations of widespread vulnerability and elevated needs? (2) At what point does it become ethically problematic to expend (considerable) resources to sustain expatriate disaster responders? (3) How ought rapid and reactive interventions be balanced with more deliberated and coordinated approaches? (4) What trade-offs are justified when interventions to address acute needs could contribute to long-term vulnerabilities? Discussion: The questions arise in light of an immense gap between available resources and widespread and elevated needs. This gap is likely unavoidable in large-scale crises and may be a source of ethical distress for both local and international responders. The analysis of ethical questions associated with crisis response can advance discussions about how relief efforts can best be designed and implemented to minimise ethical distress and improve assistance to local populations.